U-Prove Range Proof Extension - Belenkiy, Mira (Microsoft Research, 2014)
This document extends the U-Prove Cryptographic Specification by specifying set membership proofs. This allows proving that a committed value is less than, less than or equal to, greater than, or greater than or equal to another (committed) value.